Sociological reflections on the neurosciences - Pickersgill, Martyn; Keulen, Ira Van. (Bingley, U.K. : Emerald, 2011)
The neurosciences are the new cutting edge in biomedicine, and this is the first book to take a sociological imagination to this field. The neurosciences are more than a collection of scientific practices they offer up new ways of thinking about mind, body and society. Up to now, debate about the new brain sciences has been limited within sociology. As the neurosciences gain ever more traction within professional arenas, policy processes and popular culture, it is time to go beyond the primarily speculative and theoretical analyses we have had to date, and bring our sociological imagination to bear. This collection addresses this need for sociological insight through empirically rich, theoretically innovative chapters that range across methods, traditions and foci in order to cast new light on the place, role and impact of neuroscience. At the same time, this volume reflects on the insights the neurosciences have to offer sociology. With cutting-edge contributions from leading scholars from Canada, Finland, France, Germany, Israel, the UK and the USA, Sociological Reflections on the Neurosciences will be a benchmark text in the new sociology of neuroscience.
Introduction : neuroscience, identity and society / Martyn Pickersgill, Ira van Keulen -- A child surrounds this brain : the future of neurological difference according to scientists, parents and diagnosed young adults / Rayna Rapp -- Innocent machines : Asperger's syndrome and the neurostructural self / Elizabeth Fein -- Narration and neuroscience : encountering the social on the'last frontier of medicine' / Sara Shostak, Miranda Waggoner -- On the assembly line : neuroimaging production in clinical practice / Kelly Joyce -- A stone in a spaghetti bowl : the biological and metaphorical brain in neuro-oncology / Sky Gross -- Is depression a brain disorder? : neuroscience in mental health care / Ilpo Hel{u296E} --'We haven't sliced open anyone's brain yet' : neuroscience, embodiment and the governance of addiction / Julie Netherland -- Are we receptive to naturalistic explanatory models of our disease experience? : applications of deep brain stimulation to obsessive compulsive disorders and Parkinson's disease / Baptiste Moutaud -- Cognitive enhancement? : exploring Modafinil use in social context / Catherine M. Coveney -- Neuroscience and medicalisation : sociological reflections on memory, medicine and the brain / Simon J. Williams, Stephen Katz, Paul Martin -- Sociology of neuroscience or neurosociology? / Christian von Scheve -- Lost and found in translation : popular neuroscience in the emerging neurodisciplines / Jenell M. Johnson, Melissa M. Littlefield -- Field of dreams : a social history of neuroethics / Erin C. Conrad, Raymond De Vries.
Keywords: Neurosciences -- Social aspects; Social medicine